Atividade antioxidante e anti-inflamatória de extrato de casca de Pitaya (Hylocereus sp) em enterócitos in vitro - Cappelari, Monique Brigolini (My University, 2021)
Popularly known as "dragon fruit", Pitaya, especially the species Hylocereus polyrhizus (Red Pitaya), has a remarkable amount of bioactive compounds, mainly phenolic metabolites present in the peel, which rouses the interest of the pharmaceutical and nutraceutical industry. These compounds have been studied in the remediation of inflammation and oxidative damage caused by the excess production of intracellular reactive oxygen species (ROS) present in chronic conditions such as diabetes mellitus (DM). This work aimed to evaluate the antioxidant and anti-inflammatory profile of the aqueous extract of the peel of H. polyrhizus in intestinal CACO-2 cells under high glucose concentrations in vitro. It was possible to observe that the excess of glucose (35 mM) reduced cell viability by 18%, increasing the production of ROS and nitric oxide (NO) by approximately 20% and 25%, respectively, when compared to the control group. However, concentrations of 1 and 10 µg/mL of extract were effective in intestinal redox modulation, reducing the production of ROS and NO. Still, the lowest dose was the one that obtained the best response against the glucose-induced reduction in cell viability. The extract concentration that reduced by 50% the production of 2,2-diphenyl,1-picrylhydrazil free radical was 0.892 mg/mL, indicating a strong reducing potential. Furthermore, the extract presented 392.31 mg/100 g of total polyphenols and 26.27 mg/100 g of anthocyanins, which confirms that it is a good antioxidant source and an anti-inflammatory agent. These findings point to the efficacy of Pitaya peel extract against oxidative stress and inflammation caused by excess glucose in the intestinal microenvironment, showing promise for the treatment of DM, especially its long-term complications. [resumo fornecido pelo autor]
Popularmente conhecida como "fruta-do-dragão", a Pitaya, sobretudo a espécie Hylocereus polyrhizus (Pitaya vermelha), possui uma notável quantidade de compostos bioativos, principalmente metabólitos fenólicos presentes na casca, o que desperta interesse da indústria farmacêutica e nutracêutica. Esses compostos vêm sendo estudados na remediação da inflamação e dos danos oxidativos causados pelo excesso na produção de espécies reativas de oxigênio (EROs) intracelular presentes em condições crônicas, como o diabetes mellitus (DM). Esse trabalho teve como objetivo avaliar o perfil antioxidante e anti-inflamatório do extrato aquoso da casca de H. polyrhizus em células intestinais CACO-2 sob altas concentrações de glicose in vitro. Foi possível observar que o excesso de glicose (35 mM) reduziu a viabilidade das células em 18%, aumentando em cerca de 20% e 25% a produção de EROs e de óxido nítrico (ON), respectivamente, quando comparado ao grupo controle. Todavia, concentrações de 1 e 10 µg/mL de extrato se mostraram efetivas na modulação redox intestinal, reduzindo a produção de EROs e ON. Ainda, a menor dose foi a que obteve a melhor resposta frente a redução na viabilidade celular induzida pela glicose. A concentração de extrato que reduziu em 50% a produção do radical livre 2,2 difenil,1-picrilhidrazil foi de 0,892 mg/mL, indicando forte potencial redutor. Além disso, o extrato apresentou 392,31 mg/100 g de polifenóis totais e 26,27 mg/100 g de antocianinas, o que ratifica o mesmo ser uma boa fonte antioxidante e um agente anti-inflamatório. Tais achados remetem a eficácia do extrato da casca de Pitaya contra o estresse oxidativo e a inflamação causados pelo excesso de glicose no microambiente intestinal, mostrando-se promissor para o tratamento da DM, especialmente suas complicações em longo prazo. [resumo fornecido pelo autor]
Keywords: Nutrição; Diabetes; Estresse oxidativo; Antioxidantes; Polifenóis; Inflamação; Frutas